Thrombotic Microangiopathies, Thrombotic Thrombocytopenic Purpura, and ADAMTS-13 - Chapman, Kent; Seldon, Michael; Richards, Ross (Seminars in Thrombosis and Hemostasis, 2012)
Thrombotic microangiopathy (TMA) is a term used to describe a group of disorders characterized by hemolytic anemia (with prominent red blood cell fragmentation), thrombocytopenia, and thrombosis in the microvasculature. It may be used when describing patients with thrombotic thrombocytopenic purpura (TTP), hemolytic uremic syndrome, atypical hemolytic uremic syndrome, as well as a myriad of other disorders in which the TMA may be secondary to another disease or disorder. While limited information exists as to the exact cause of microthrombosis in many TMA, recent advances have been made in the understanding of TTP and its pathophysiology. This progress can be attributed to discovery of the von Willebrand factor cleaving protease ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13), whose absence in TTP has given the disorder a distinct molecular identity. The discovery of this metalloprotease has prompted a significant amount of research relating to its role in TTP as well as its general function in hemostasis. The exact mechanisms by which this metalloprotease achieves its role are slowly being understood and these now provide other avenues by which TMA may occur.
Keywords: ADAMTS-13; thrombotic thrombocytopenic purpura; thrombotic microangiopathy; CD36; von Willebrand factor